Local shape adjustment and residual stresses of integrally stiffened panel induced by mechanical hammer peening. (7th April 2023) - Lan, Liangyun; Niu, Hongbing; Cui, Yanan; Chen, Xingzhao
Abstract: Integrally stiffened panels of high performance aluminium alloys are widely applied in the aerospace field because of their lightweight, high stiffness and excellent structural reliability. However, these advantages also bring about some problems that perplex the integral forming, e.g., local contour of these panels after forming always does not meet the requirements. To overcome this problem, we built a new forming equipment-mechanical hammer peening to trim the local contour of integrally stiffened panels. Based on the experimental and finite element analyses, it is demonstrated that this set-up has an enough peening capability to trim the local contour of panels. The local forming mechanism is that the plastic deformation of peened stiffener restricts the elastic recovery of the panel skin. However, the peened stiffener exhibits obvious longitudinal tensile residual stresses, and the maximum always exists at the rim of the peening area. To obtain maximum local convex curvature of the panel skin and limit the tensile residual stress of the peened stiffener, the penetration depth of PEEQ (equivalent plastic strain) into the stiffener should be aimed at around half of the height of stiffener. That is, under the present experimental set-up with the hammer head mass of 10 kg, the peening velocity is better to set at around 6 m/s.